2023
DOI: 10.1287/mnsc.2022.4400
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Optimality of Base-Stock Policies for Perishable Inventory Systems

Abstract: We consider periodic review perishable inventory systems with a fixed product lifetime. Unsatisfied demand can be either lost or backlogged. The objective is to minimize the long-run average holding, penalty, and outdating cost. The optimal policy for these systems is notoriously complex and computationally intractable because of the curse of dimensionality. Hence, various heuristic replenishment policies are proposed in the literature, including the base-stock policy, which raises the total inventory level to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Also, they combined the fixed and known lead time with some unknown demand distribution parameters to develop a learning algorithm with a linearly dependent regret bound. In a sporadic examination of perishable inventory procedures with a specified yield lifetime, Bu et al [43] included a base-stock policy and partial backlogging. They showed that an easy base-stock model was asymptotically optimal for enlarging any one out-of-yield lifetime, order population extent, unit liability cost, and unit outdating expense.…”
Section: Review Of Backlogged and Disruptions-induced Partially Backl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they combined the fixed and known lead time with some unknown demand distribution parameters to develop a learning algorithm with a linearly dependent regret bound. In a sporadic examination of perishable inventory procedures with a specified yield lifetime, Bu et al [43] included a base-stock policy and partial backlogging. They showed that an easy base-stock model was asymptotically optimal for enlarging any one out-of-yield lifetime, order population extent, unit liability cost, and unit outdating expense.…”
Section: Review Of Backlogged and Disruptions-induced Partially Backl...mentioning
confidence: 99%
“…Wang et al[48] base-stock NA truncated and convoluted demand NA Present study base-stock supply-side selling price dependent partial Figure1. A comparative analysis of the existing literature on inventory models[9,11,16,18,26,31,32,39,41,43].…”
mentioning
confidence: 99%
“…Given these challenges, many studies have proposed heuristic and approximately optimal policies. These approximate policies include base stock or TIS (total‐inventory‐to‐S) policies that bring up the total inventory level to a fixed value (Bu et al., 2022; Cooper, 2001; Nahmias, 1976; Nandakumar & Morton, 1993); NIS (new‐inventory‐to‐S) policies that order a pre‐determined quantity of fresh units in each period (Brodheim et al., 1975; Deniz et al., 2010); and false(s,Sfalse)$(s,S)$‐type policies (Nahmias, 1978) when fixed ordering costs are considered.…”
Section: Related Literaturementioning
confidence: 99%